Fostering Employee Creativity In Software Houses: Exploring The Influence Of Ethical Leadership, LMX, And Employee Feedback-Seeking Behavior - Ajmal, Dr. Muhammad; Khan, Dr. Imran; Islam, Azmat (Migration Letters, 2024)
Today’s knowledge-based IT industry provokes volatile challenges due to fast-paced changes in a competitive global landscape. Creative performance, a radical source of attaining, promoting, and sustaining a competitive edge, contributes to the long-term sustainability of this industry. The purpose of study is to identify the antecedents of employee creative perfromace with respect to ethical leadership and LMX .Data is collected from software houses in Pakistan registered in PSEB from three hundred and twenty (320) leader-employee dyads. Current research is conducted by adopting a cross-sectional design. Information was obtained from, leaders and their relevant subordinates by distributing a questionnaire online so as to reduce common method biases and physical visit as well. Results signify that leader-member exchange, ethical leadership and employee feedback-seeking behavior perform a dynamic function in the software industry in enhancing employee creativity. To the extent of pragmatic implications, findings suggest that to provoke creative performance among employees, leaders of software houses must uphold these proposed variables by considering them as an integral part of their organizational strategy.Study is to evaluate and understand how ethical leadership generate influence creative performance, particularly the way how ethical leadership affects employee creative performance through the intermediating position of LMX and employee feedback-seeking behavior.